2014
DOI: 10.4103/1947-2714.141632
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of shock index and modified shock index with the outcome of adult trauma patients: A prospective study of 9860 patients

Abstract: Background:Triage at emergency department is performed to identify those patients who are relatively more serious and require immediate attention and treatment. Despite current methods of triage, trauma continues to be a leading cause of morbidity and mortality.Aims:This study was to evaluate the predictive value of shock index (SI) and modified shock index (MSI) for hospital mortality among adult trauma patients.Materials and Methods:In this prospective longitudinal study, all adult patients who sustained tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 10 publications
2
73
1
1
Order By: Relevance
“…For each indicator, we defined the different cut-off values of hemodynamic instability according to previous research (131517). Hemodynamic instability was defined as an SI equal to or greater than 1, an MSI equal to or greater than 1.3, and an Age SI equal to or greater than 50.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each indicator, we defined the different cut-off values of hemodynamic instability according to previous research (131517). Hemodynamic instability was defined as an SI equal to or greater than 1, an MSI equal to or greater than 1.3, and an Age SI equal to or greater than 50.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research suggested that SI multiplied by age (Age SI) is a better predictor of mortality following traumatic injury of an elderly patient (15). Another investigator proposed use of the modified shock index (MSI), the ratio of heart rate to mean blood pressure, as a more accurate predictor than systolic blood pressure, heart rate, and SI (1617). However SI, MSI, and Age SI were developed and validated for different populations (111213).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SI and MSI after PCI and treatment were not evaluated. Singh et al [15] pointed out that MSI of 0.7 or greater also predicts poor outcome in patients with trauma. This study only divided the patients into 2 groups by a cut point of MSI of 1.4 as the MSI less than 0.7 was only seen in 2 cases without 7-day MACE.…”
Section: Limitationsmentioning
confidence: 98%
“…Some studies have found that MSI is a better predictor than SI for the outcome in adult patients with trauma [14,15]. However, the predictive value of MSI has not been evaluated in the patients with STEMI.…”
Section: Introductionmentioning
confidence: 95%
“…35 However, to the best of our knowledge, only one small (n=160), retrospective study compared the shock index with the modified shock index for the short-term prediction of a combined clinical endpoint (all-cause mortality, life-threatening arrhythmias, cardiogenic shock, and heart failure) in patients after STEMI. 36 The authors of this study found that both the shock index and the modified shock index were independent predictors of MACE, but the odds ratio of the modified shock index was numerically higher than that of the shock index.…”
Section: Shock Index Vs Modified Shock Indexmentioning
confidence: 99%